Two newly discovered tenth-century Organa - Varelli, G (Cambridge University Press, 2013)
In the tenth century, when the earliest chant books were being compiled in the heart of the Carolingian Empire and polyphonic music was entering the realm of theoretical speculation in the anonymous writings of Musica enchiriadis and Scolica enchiriadis, organa were also being notated for performance outside music treatises. We would not know this, were it not for a two-voice organum on an antiphon for Saint Boniface written in the first decades of the tenth century on the last page of a long-neglected manuscript, now in the British Library. A second notated antiphon, Rex caelestium terrestrium, provides elements for a reconstruction of a further, ‘hidden’, organum. These newly identified organa shed light on a significant phase in Western music history, being the sole evidence from the tenth century of a polyphonic practice before the great eleventh-century collection of organa from Winchester.